2021
DOI: 10.3390/ma14133522
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Flexural Behavior of Fiber-Reinforced Concretes Exposed to Moderate Temperatures

Abstract: The use of synthetic fibers in fiber-reinforced concretes (FRCs) is often avoided due to the mistrust of lower performance at changing temperatures. This work examines the effect of moderate temperatures on the flexural strengths of FRCs. Two types of polypropylene fibers were tested, and one steel fiber was employed as a reference. Three-point bending tests were carried out following an adapted methodology based on the standard EN 14651. This adapted procedure included an insulation system that allowed the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The distribution of C-S-H decreases voids and boosts the specimen's strength. The rather porous textured features displayed in this matrix indicate a level of porosity typical of regular mixtures (Castillo-Lara et al, 2020;Sanchez-Echeverri et al, 2020;Zhang et al, 2020;Caballero-Jorna et al, 2021;Aisheh et al, 2022;Najm et al, 2022). Depending on the amount of latex in the mix, modified mixes on the other hand have displayed more compact characteristics.…”
Section: Sem Morphologymentioning
confidence: 86%
“…The distribution of C-S-H decreases voids and boosts the specimen's strength. The rather porous textured features displayed in this matrix indicate a level of porosity typical of regular mixtures (Castillo-Lara et al, 2020;Sanchez-Echeverri et al, 2020;Zhang et al, 2020;Caballero-Jorna et al, 2021;Aisheh et al, 2022;Najm et al, 2022). Depending on the amount of latex in the mix, modified mixes on the other hand have displayed more compact characteristics.…”
Section: Sem Morphologymentioning
confidence: 86%
“…The structural integrity of FRC is mainly based on the properties of the fibres, such as fibre geometry, the orientation of the fibre in the concrete, the type of fibre and the volume fraction of the fibre [ 6 , 7 , 8 , 9 , 10 ]. Several studies have addressed that incorporating fibres in concrete can improve properties such as impact resistance, flexural strength, thermal resistance, fatigue resistance and ductility [ 11 , 12 , 13 , 14 , 15 ]. Brandt [ 16 ] evaluated the orientation effect of parallel fibre systems and concluded that the maximum fracture energy was due to the fibres being subjected to axial tension.…”
Section: Introductionmentioning
confidence: 99%